Meningkatkan Literasi dan Numerasi Siswa di SDN 5 Kalibarumanis Melalui Pembelajaran Kreatif dalam Program Kampus Mengajar - Tasya Madinah; Astri Widyaruli Anggraeni (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
The Kampus Mengajar Program is an initiative by the Ministry of Education, Culture, Research, and Technology of Indonesia aimed at improving the quality of education in elementary schools, particularly in literacy and numeracy. This study aims to evaluate the effectiveness of this program at SDN 5 Kalibarumanis through a creative learning approach. Implemented programs include Puzzle Mame (Metaphor Majas), TTS Listening to Stories, and the Making of 3D Shape Nets. The results show that this creative approach successfully increased students' interest, motivation, and literacy and numeracy skills. Collaboration with class teachers also positively contributed to the program's success. Based on these findings, it is recommended that this creative learning approach be further developed and implemented in other schools to enhance overall educational quality.